2005
DOI: 10.1111/j.1463-5224.2005.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconjunctival effects of diabetes mellitus in dogs

Abstract: Diabetic cataractous dogs have significantly altered keratoconjunctival characteristics compared to nondiabetic cataractous and nondiabetic noncataractous dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
3
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 32 publications
8
66
3
10
Order By: Relevance
“…In studies of rats with induced type 1 diabetes mellitus, tear production and corneal sensitivity have been noted to decline approximately 5 weeks after induction and remain low thereafter . Similar decreases in corneal sensitivity and tear production have also been shown in diabetic people and dogs . The mechanism underlying this decrease is currently unknown but is postulated to be the result of a peripheral neuropathy affecting both the sensory afferent nerves innervating the ocular surface and those innervating the lacrimal gland.…”
Section: Discussionmentioning
confidence: 80%
“…In studies of rats with induced type 1 diabetes mellitus, tear production and corneal sensitivity have been noted to decline approximately 5 weeks after induction and remain low thereafter . Similar decreases in corneal sensitivity and tear production have also been shown in diabetic people and dogs . The mechanism underlying this decrease is currently unknown but is postulated to be the result of a peripheral neuropathy affecting both the sensory afferent nerves innervating the ocular surface and those innervating the lacrimal gland.…”
Section: Discussionmentioning
confidence: 80%
“…The clinical finding of an increased prevalence of KCS in diabetic dogs compared to nondiabetic dogs after phacoemulsification is not surprising. Both quantitative and qualitative tear abnormalities may predispose diabetic dogs to KCS more so than nondiabetic dogs after cataract surgery . Both human and canine studies have shown through corneal aesthesiometry that there is a trend toward lower corneal sensation in the diabetic cataractous group compared to the nondiabetic cataractous group, likely resulting in a decrease in the reflex component of tear production and a subsequent overall decrease in aqueous tear volume .…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of canine DM are insulin dependent, and therefore behave similarly to type 1 DM with an autoimmune etiology in human patients . Established ocular manifestations of canine DM include cataracts, corneal endothelial cell loss, endothelial cell pleomorphism and polymegathism, decreased corneal sensitivity, increased susceptibility to keratoconjunctivitis sicca (KCS), and to a lesser extent, retinopathy due to microaneurysms . In addition, DM has been associated with neuropathies in both dogs and humans …”
Section: Introductionmentioning
confidence: 99%